Purview of Trade Dress Protection in India (GLS Law Journal, 2025)
The article explores the concept of trade dress protection in the context of India's evolving legal landscape. Trade dress, the overall visual appearance and aesthetic identity of a product, is gaining significance due to its role in brand identity and consumer recognition. This article examines the origins of trade dress, its importance in consumer protection, and the challenges it poses in the Indian legal framework, where explicit provisions for trade dress are limited. Through a comprehensive analysis of judicial precedents, the article highlights landmark cases that have contributed to the development of trade dress protection in India, focusing on aspects such as packaging, shape, color combinations, and product form. The objective of trade dress is to prevent confusion among consumers and protect the unique features that distinguish a product in the market. While India is catching up with international norms, there is a need for a more robust and coherent legal framework to safeguard trade dress. The article concludes by emphasizing the importance of enhancing enforcement mechanisms and fostering a strong culture of trade dress protection to promote innovation, maintain fair competition, and instill consumer confidence in the marketplace.
Keywords: Trade Dress Protection; Brand Identity; Consumer Recognition; Indian Legal Framework; Judicial Precedents